The effects of cognitive-behavior therapy for depression on repetitive negative thinking: A meta-analysis. (July 2018) - Spinhoven, Philip; Klein, Nicola; Kennis, Mitzy; Cramer, Angélique O.J.; Siegle, Greg; Cuijpers, Pim; Ormel, Johan; Hollon, Steve D.; Bockting, Claudi L.
Abstract: It is not clear if treatments for depression targeting repetitive negative thinking (RNT: rumination, worry and content-independent perseverative thinking) have a specific effect on RNT resulting in better outcomes than treatments that do not specifically target rumination. We conducted a systematic search of PsycINFO, PubMed, Embase and the Cochrane library for randomized trials in adolescents, adults and older adults comparing CBT treatments for (previous) depression with control groups or with other treatments and reporting outcomes on RNT. Inclusion criteria were met by 36 studies with a total of 3307 participants. At post-test we found a medium-sized effect of any treatment compared to control groups on RNT (g = 0.48; 95% CI: 0.37–0.59). Rumination-focused CBT: g = 0.76, <0.01; Cognitive Control Training: g = 0.62, p < .01; CBT: g = 0.57, p < .01; Concreteness training: g = 0.53, p < .05; and Mindfulness-based Cognitive Therapy: g = 0.42, p < .05 had medium sized and significantly larger effect sizes than other types of treatment (i.e., anti-depressant medication, light therapy, engagement counseling, life review, expressive writing, yoga) (g = 0.14) compared to control groups. Effects on RNT at post-test were strongly associated with the effects on depression severity and this association was only significant in RNT-focused CBT. Our results suggest that in particular RNT-focused CBT may have a more pronounced effect on RNT than other types of interventions. Further mediation and mechanistic studies to test the predictive value of reductions in RNT following RNT-focused CBT for subsequent depression outcomes are called for. Highlights: We examined the effects of treatment for depression on repetitive negative thinking (RNT). Treatment had a robust medium effect on RNT compared to various control conditions. Cognitive-behavior therapy (CBT) had a larger effect than alternative treatments. Effects on RNT were strongly associated with those on depression. This association was only significant in CBT treatments focusing on RNT.